Evaluasi Program Operasi Pangan Riau Makmur (OPRM) di Kabupaten Pelalawan Tahun 2010-2013 - Zamira Ulfa; Muhammad Ridwan (Nakhoda: Jurnal Ilmu Pemerintahan, 2014)
Rice is the staple food of the people of Indonesia , especially in Riau , thus forming Rice Production Enhancement Program in order to increase rice production in Riau , namely Riau Makmur Food Operations program covering Improved Farming Index ( IP 100 - IP 200) , Print new Rice and Rehabilitation Abandoned rice fields . This study aimed to evaluate the implementation of the Programme of Food Operations Riau Makmur in the regency. This study focused on Pelalawan because considering the number of problems that occur in the field , namely the realization of Food Operations Program Riau Makmur which is not in accordance with the target . The research problem is how the human resources , infrastructure , program outcomes and the factors inhibiting Food Operations Riau ( OPRM ) . Based on this background , the study aims to identify the implementation of Food Operations Riau Makmur ( OPRM ) and to identify the factors that affect the implementation of Operation inhibiting Food Riau Makmur (OPRM). This research is descriptive in which researchers provide a description or picture of the phenomenon or social phenomena studied by describing the independent variables systematically and accurately . Methods of data collection is done by observation and interview . The results of this study indicate that in Pelalawan unsuccessful melaksanakaan Food Operations Program Riau Makmur ( OPRM ) seen from the indicators of human resources , infrastructure dann inadequate results and factors - factors that influence that human resources are still low , inadequate infrastructure , lack of role of field workers and less active in the Coordination Node Pos district and village level.